Theories Involved in Recognizing and Implementing International Law in Domestic Contexts - Thilakarathna, K.A.A.N.; Jayarathna, Nisanka (www.iiste.org, 2021)
The impact of international law on the domestic legal system has never being more visible and potent as we see it today. While this being the case, international law itself does not provide a mechanism as to how international law should be absorbed in to the domestic legal system and that question is left for the country in question to decide. In selecting an appropriate method for introducing international law into the domestic legal system, the theoretical aspirations of monism and dualism has been in the forefront of many books and articles that have been written on the subject, yet it has been rejected as being failing to appraise the actual practises of the countries in question when adopting a particular mechanism for bringing international law into the domestic legal system. This article there for explores the reasons as to why monism and dualism has failed to introduced a methodology in bringing international law into the domestic context and what theoretical explanations could be provided for such failure with a conclusion on a more pragmatic approach in choosing the middle way between monism and dualism.
Keywords: Monism; Dualism